(untitled) (CIPEEX, 2025)
Introduction: Thrombosis is a multifactorial condition that can be exacerbated by the use of oral contraceptives due to the hemostatic changes they cause. This risk represents a significant public health problem, especially among women of reproductive age. Objective: To review the literature to see if the use of oral contraceptives is associated with a higher risk of thrombosis. Methodology: This literature review was conducted using the PICO strategy. Studies were selected from the SciELO, PubMed, and BVS databases. The search used the following descriptors combined with Boolean operators: oral contraceptive OR oral hormonal contraceptive AND risk AND thrombosis. Cross-sectional studies published in English were included. A total of 42 studies were identified, of which 7 met the eligibility criteria and were included in this review. Results: Analysis of the 7 studies that met the inclusion criteria showed that women using combined oral contraceptives have a significantly higher risk of thrombosis compared to non-users. This increased risk is related to the drug formulation, the dose used, and the individual biological characteristics of the women. Conclusion: The risk of thrombosis associated with the use of combined oral contraceptives is influenced by the formulation, dose, and individual characteristics of the users. Studies of this type are promising for deepening the understanding of the causes and risk factors associated with the use of these medications. The importance of prevention strategies aimed at reducing the impact of thrombosis on public health is also highlighted.